2005
DOI: 10.1016/j.nuclphysb.2005.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and Goldstone effects in a QCD with two flavours of adjoint quarks

Abstract: We study QCD with two Dirac fermions in the adjoint representation at finite temperature by Monte Carlo simulations. In such a theory the deconfinement and chiral phase transitions occur at different temperatures. We locate the second order chiral transition point at β c = 5.624(2) and show that the scaling behaviour of the chiral condensate in the vicinity of β c is in full agreeement with that of the 3d O(2) universality class, and to a smaller extent comparable to the 3d O(6) class. From the previously dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
95
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(109 citation statements)
references
References 33 publications
11
95
0
1
Order By: Relevance
“…This behavior has also been found in QCD with adjoint quarks, i.e. ψ ψ ∼ c 0 + c 1 (m l /T ) 1/2 [17,18]. Our current analysis of the quark mass dependence of the chiral condensate is not yet accurate enough and has not yet been performed at small enough quark masses to verify this behavior explicitly.…”
Section: Finite Temperature Simulationsmentioning
confidence: 63%
See 1 more Smart Citation
“…This behavior has also been found in QCD with adjoint quarks, i.e. ψ ψ ∼ c 0 + c 1 (m l /T ) 1/2 [17,18]. Our current analysis of the quark mass dependence of the chiral condensate is not yet accurate enough and has not yet been performed at small enough quark masses to verify this behavior explicitly.…”
Section: Finite Temperature Simulationsmentioning
confidence: 63%
“…For this purpose we monitor the value of the kaon mass and the strange pseudo-scalar 2 , m ss . In the continuum limit the physical point is then given as (m ps r 0 , m K r 0 ) = (0.321(5), 1.177 (18)) where the error reflects the uncertainty in r 0 [13]. At this point the strange pseudo-scalar in units of r 0 is given by m ss r 0 = 1.631 (24).…”
Section: B the Physical Pointmentioning
confidence: 99%
“…In the case of adjoint fermions, lattice simulations have shown that chiral symmetry is restored at a substantially higher temperature than the deconfinement temperature, with the ratio of critical temperatures T c /T d around 7.8 [82,83].…”
Section: Connection Of Chiral Symmetry Breaking and Confinementmentioning
confidence: 99%
“…Such groups are formed by diagrams (7-11), (12)(13), (14)(15)(16)(17)(18), (19)(20), (21)(22)(23) in Fig.2, diagrams (3-7), (8)(9), (10)(11)19) in Fig.4 and diagrams (1-2), (3-4) in Fig.5.…”
Section: Computation and Resultsmentioning
confidence: 99%